Konseling Kelompok Teknik Assertiveness training Untuk Mereduksi Perilaku People pleaser Siswa - Sholekah, Anik; Jawandi, Ahmad; Putro, Eko adi (Advice: Jurnal Bimbingan dan Konseling, 2025)
The purpose of this study was to determine the effectiveness of group counseling services with assertiveness training techniques in reducing people pleaser behavior in class XI D3 students of SMA Negeri Colomadu. People pleasers are individuals who tend to prioritize the needs of others above themselves, find it difficult to refuse requests, are afraid of being shunned, and often ignore personal happiness in order to gain acceptance and approval from others. The research method used was an experiment with a one group pretest-posttest design. The subjects of this study were 8 class XI D3 students selected by purposive sampling. The instrument used in this study was a questionnaire that measured the level of people pleaser behavior of students before and after being given group guidance with assertiveness training techniques. The data obtained were analyzed using the Wilcoxon test, the sig. value was 0.012 <0.05, so H0 was rejected and Ha was accepted. The results showed that there was a significant decrease in people pleaser behavior of students after participating in group counseling with assertiveness training techniques. Keyword: Group counseling, Assertiveness training techniques, People pleaser